High‐energy density of Pb0.97La0.02(Zr0.50Sn0.45Ti0.05)O3 antiferroelectric ceramics prepared by sol‐gel method with low‐cost dibutyltin oxide. Issue 4 (14th September 2018) - Dan, Yu; Xu, Haojie; Zhang, Yangyang; Zou, Kailun; Zhang, Qingfeng; Lu, Yinmei; Chang, Gang; Zhang, Qi; He, Yunbin
Abstract: Lead lanthanum zirconate stannate titanate (PbLa(ZrSnTi)O3 ) antiferroelectric (AFE) ceramics are widely used in dielectric capacitors due to their superior energy‐storage capacity. Generally, these ceramics can be synthesized by solid‐state reaction and sol‐gel methods. Ceramics prepared using the sol‐gel method have a purer phase than those prepared using the solid‐state reaction method because the sol‐gel method can avoid the segregation of Sn. However, because the commonly used raw material tin acetate is very expensive, the preparation of PbLa(ZrSnTi)O3 AFE ceramics via the sol‐gel method is not cost‐effective, which prevents the use of sol‐gel method for manufacturing PbLa(ZrSnTi)O3 in a large scale. In this work, low‐cost dibutyltin oxide instead of expensive tin acetate is used to synthesize Pb0.97 La0.02 (Zr0.50 Sn0.45 Ti0.05 )O3 (PLZST) nanopowders, and single‐phase powders with a perovskite structure and average grain size of 200 nm are obtained at a calcination temperature of 580°C. In addition, dense PLZST AFE ceramics with a pure perovskite structure are obtained by sintering the PLZST nanopowders at temperatures as low as 1100°C. The sintered PLZST ceramics exhibit a room‐temperature recoverable energy‐storage density as high as 1.93 J/cm 3 with an efficiency of 75%, which varies only slightly in the temperature range of 20‐120°C. The high energy‐storage density (>1.9 J/cm 3 ) over a wide temperature range illustrates that the sol‐gel‐derived PLZST ceramics with low‐cost dibutyltin oxide are quite promising for manufacturing pulse power capacitors.